Konsep Kecerdasan Spritual dalam Pemikiran Ary Ginanjar Agustian dan Relevansinya terhadap Pengembangan Pendidikan Islam - Panuntun, Selamet (IEMJ: Islamic Education and Management Journal, 2024)
The study of spiritual intelligence is becoming increasingly important in the midst of modernisation, which is marked by the level of development of science and technology. Through this research, it is important to know how to grow spiritual intelligence in the view of Ary Ary Ginanjar Agustian, and how the implications in Islamic education. With the focus of the problem, this research includes library research, conducted by reading, examining, and understanding several sources including: books, scientific works, journals, tabloids, and other sources, with the aim of making it easier to obtain data.VAnalysis of data using descriptive and interpretative techniques. The results show that if a person defines himself as part of the religious community, spiritual intelligence can certainly educate his heart to establish a relationship of intimacy with God's presence. Then, the horizontal implication is that spiritual intelligence educates the heart into good manners and civilised morals.